(untitled) (ASEAN Engineering Journal, 2023)
The purpose of this study is to examine the major economic challenges concerning budgets and costs associated with sustainable green buildings (SGBs) in Jordan over their life cycle. This research is significant because it will add to the literature in this area and give interested parties a glimpse into the current state of economic issues facing SGBs in Jordan and affect the adoption of this building technology there. Based on a thorough review of the literature, data was gathered using a qualitative technique based on in-depth semi-structured interviews with 32 professionals of SGBs in Jordan. According to the findings of this study, the main economic challenge in the design stage is the "High initial cost,” the main economic challenge in the construction stage is “Budget and cost of materials, working techniques, and labor,” the most significant economic challenge in the operational stage is “Long-term cost recovery,” and the main economic challenge in the maintenance stage is “Budget and cost challenges.” Despite the importance of this research in terms of adding to the current body of knowledge by examining the economic challenge of SGBs in Jordan as a developing country during the life cycle stages, the findings are based on qualitative data collected from highly experienced specialists in this sector. Therefore, a quantitative data collection using various evaluation approaches is recommended for further research.